Keikutsertaan Perempuan Dalam Program Penanggulangan Kemiskinan Pada Masyarakat Matrilineal Minangkabau - Sarmiati, Sarmiati (Mitra Gender (Jurnal Gender dan Anak), 2018)
Research on the Participation of Women in Poverty Reduction Programs in matrilineal Minangkabau society was done in Padang West Sumatera. The purpose of this study was to describe, explain and analyze the participation of women in poverty reduction, using the concept of silent group (muted group). Silent group is the person or group of women who followed P2KP in Padang. This study used the constructivist paradigm with a qualitative approach. The study found that almost in every village who get this program, the involvement of women exceeds the minimum rate set by the program. The program set a minimum 30% involvement of women in each cycle of activity. When there is a cycle of activities that do not involve women, or not attended by at least 30% of women, then these activities must be repeated. Although the minimum number set by the program reached, but the silence of women is still there. Theoretically, this study shows that the program PNPM Urban (P2KP) found groups of silence, there are women who get involved in the program, but not maximized in doing poverty reduction. For that is expected this research can move the hearts of other researchers to explore this issue through the theory and concepts are the same. In practical given the poverty rate in Indonesia, West Sumatera in particular, especially the poverty being experienced by women, it needs serious attention and treatment from the government in cooperation with the community and as well as women’s activeness in addressing it.